Illustrated dictionary of parasitology in the post-genomic era - Elsheikha, Hany; Jarroll, Edward L. (Caister Academic Press, 2017)
With over 4500 entries and more than 170 figures this volume reflects recent, ground-breaking advances in parasitology research. The authors have provided, in a single-volume, an up-to-date glossary of the terminology encountered in contemporary parasitology literature. The dictionary also covers many pertinent terms from related fields of veterinary medicine and life sciences, including microbiology, genetics, biochemistry, biotechnology, infectious diseases, epidemiology, zoonoses, public health, molecular biology, zoology, pharmaceutical science, environmental science, taxonomy and populati.